Is Ancestor veneration the most universal of all world religions? A critique of modernist cosmological bias - Reuter, Thomas (UI Scholars Hub, 2014)
Research by anthropologists engaged with the Comparative Austronesia Project (Australian National University) has amassed an enormous data set for ethnological comparison between the religions of Austronesian-speaking societies, a language group to which nearly all Indonesian societies also belong. Comparative analysis reveals that ancestor veneration is a key-shared feature among